2020
DOI: 10.3389/fonc.2019.01456
|View full text |Cite
|
Sign up to set email alerts
|

Heart and Cardiac Substructure Dose Sparing in Synchronous Bilateral Breast Radiotherapy: A Dosimetric Study of Proton and Photon Radiation Therapy

Abstract: Background: Synchronous bilateral breast cancer (SBBC) is rare. The purpose of this study was to compare the dosimetric differences in intensity-modulated radiation therapy (IMRT), volumetric-modulated arc therapy (VMAT), helical tomotherapy (HT), and intensity-modulated proton therapy (IMPT) to find an optimal radiotherapy technique for bilateral breast cancer radiotherapy. Methods: For 11 patients who received synchronous bilateral whole-breast irradiation without local lymph nodal regions, six plans were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…In the same study, VMAT-DIT plans demonstrated higher compatibility and significantly decreased lung, heart, LV, and LAD doses than VMAT-MIT plans. 16 In our study, the V25Gy value was 3.9% in MIT and 4% in DIT and the dose for the heart was acceptable.…”
Section: Discussionsupporting
confidence: 44%
“…In the same study, VMAT-DIT plans demonstrated higher compatibility and significantly decreased lung, heart, LV, and LAD doses than VMAT-MIT plans. 16 In our study, the V25Gy value was 3.9% in MIT and 4% in DIT and the dose for the heart was acceptable.…”
Section: Discussionsupporting
confidence: 44%
“…It has been proven that volumetric modulated arc therapy (VMAT) can improve the quality of the plan and the delivery e ciency in bilateral breast cancer [8][9][10]. A previous study found that the partial-arc VMAT plans signi cantly reduced the cardiopulmonary dose compared with the whole-arc VMAT plans in unilateral breast radiotherapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that volumetric modulated arc therapy (VMAT) can improve the quality of the plan and the delivery efficiency in bilateral breast cancer [ 8 10 ]. A previous study found that the partial-arc VMAT plans significantly reduced the cardiopulmonary dose compared with the whole-arc VMAT plans in unilateral breast radiotherapy [ 11 ].…”
mentioning
confidence: 99%